Women students in political organizations : appropriating and reinterpreting apartheid history in post apartheid South Africa. - Mashigo, Thembelihle N. C. (My University, 2014)
This research project explored how young women involved in political organizations make sense of apartheid history and how they appropriate that history into their identities. Nine black women students who were involved in political organizations were interviewed from the University of Witswatersrand. The women that were chosen participated in a narrative style interview about their lives and the history of apartheid. The data were then analyzed using narrative thematic analysis and organised in the temporal zones of past, present and future. The analysis revealed the complexities of race, class and gender and how these are embodied, enacted and made sense of in the construction and reconstruction of the identities of these young women. In imagining and reflecting on the apartheid past, race was understood through both distant, public narratives and through personal and intimate family narratives. Gendered roles or positions were talked about in reference to three thematic symbols of women as nurturers, iconic wives and heroes. In progression from the apartheid past and its particular, separated and structured understanding of race and gender, the journey into the present and future, reflects increasingly complex, dynamic and multilayered understandings. In particular, the conflation of race and class under apartheid is beginning to fragment and these young women are thinking through their positionality in terms of personal class mobility and simultaneous identification as black and committed to the continuation of race struggles. It is also very clear that the question of gender equality is now very prominent for these young women as they navigate their roles in political leadership in the present and envisage themselves in the future.
Keywords: Women college students--Political activity--South Africa.; College students, Black--South Africa--Psychology.; Political socialization--South Africa.; Apartheid--South Africa--Psychological aspects.